Analysis of Lavender Flower Extract (Lavandula Angustifolia) as a Natural Larvicide for the Control of Aedes Aegypti Larvae - Kenza Farah; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Dengue fever is a disease caused by a virus inside the Aedes aegypti mosquito. One way to prevent the spread of dengue fever is by breaking the life cycle of mosquitoes. One cycle that is very easy to break in the chain of mosquito life is the larval cycle. One of the powerful larvicides to kill Aedes aegypti larvae is extracted from lavender flowers (Lavandula angustifolia). The purpose of this study was to determine the effectiveness of lavender flower extract (Lavandula angustifolia) as a natural larvicide for Aedes aegypti larvae. The method used in this study was a sample of 60 larvae and distilled water. The results obtained show that lavender extract (Lavandula angustiolia) is effective in controlling the conclusion of this study is that lavender extract (Lavandula angustifolia) as a larvicide can kill Aedes aegypti mosquito larvae. The mortality rate of Aedes aegypti larvae, according to the results of the study, is strongly influenced by the number of concentrations drops of extract and the number of larvae in each container.